Analysis of Current Cold-Case Investigation Practices and Factors Associated with Successful Outcomes, 2008-2009 - Davis, Robert C. ([Verlag nicht ermittelbar], 2016)
These data are part of NACJD's Fast Track Release and are distributed as they there received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except of the removal of direct identifiers. Users should refer to the accompany readme file for a brief description of the files available with this collections and consult the investigator(s) if further information is needed.To assess the current practices in cold-case investigations, this study utilized a national online survey of law enforcement agencies (Cold Case Survey Data, n = 1,051) to document the range of ways in which cold-case work is conducted and assess how this organization affects cold-case clearance rates. In November 2008, the chiefs of police in the sample were sent a letter explaining the purpose of the survey and inviting them to participate. Potential respondents were directed to the web-based survey instrument through a provided web address. The results from the national survey were used to select sites for an analysis of case files. Researchers chose three jurisdictions that conducted a large number of cold-case homicide investigations: the District of Columbia, Baltimore, Maryland, and Dallas, Texas (Cold Case Homicide Data, n = 429). To these three sites, researchers added Denver, Colorado (Cold Case Sexual Assault Data, n = 105) because it had received a Department of Justice grant to conduct testing of DNA material in sexual assault cold cases. At all four sites, cold cases were examined for seven categories of data including victim's characteristics, crime context, motivation, human capital, physical evidence, basis for cold-case investigations and cold-case actions.